PERAN ETNOMATEMATIKA DALAM KONSEP DASAR PEMBELAJARAN MATEMATIKA - Aji Permana Putra; dias Prasetyo (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan Universitas Cokroaminoto Yogyakarta, 2022)
The role of Science and Technology (IPTEK) in the development of the times has a significant contribution. In the midst of the development of educational technology, the education curriculum is also involved in the development of culture that is integrated in school learning with the aim that students can become a generation with character and able to maintain and preserve culture as the foundation of national character. The education curriculum is required to always develop in accordance with the progress of the times as well as cultural involvement in learning in schools in order for students to be able to recognize the culture of the ancestors who have character and able to maintain and preserve culture as the foundation of the nation's educational character. Cultural practice allows for the inculcation of mathematical concepts into reality. More specifically in the learning of mathematics there are factors that affect the learning achievement of learners. These factors are attached to the ability of learners in learning mathematics. The role of ethnomatics is able to evoke the understanding of learners in the process of learning mathematics is certainly related to the cultural treasures that are inherent in the society where learners and schools are located. Ethnomathematics brings out cultural wisdom so that it is able to motivate students in learning mathematics. The description of the study in this article includes the exploration of ethnomathematics from various areas that show the relationship between ethnomathematics and the basic concepts of mathematics learning